2021
DOI: 10.4149/km_2014_6_337
|View full text |Cite
|
Sign up to set email alerts
|

Relation between microstructural features and mechanical properties in oxygen free high conductivity copper after Equal-Channel Angular Pressing

Abstract: An oxygen free high conductivity (OFHC) copper was subjected to maximum 13 ECAP passes to achieve a sufficiently high degree of deformation. Strength properties (yield stress and ultimate tensile strength) show obvious increase up to the 4 th pass. In the 6 th ECAP pass, the yield stress and ultimate tensile strength are stabilized at a maximum of 449 MPa. Microstructure studies showed that the 1 st ECAP pass caused a significant increase of dislocation density. These dislocations are arranged in cells, formin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Severe plastic deformation (SPD) methods applied to metals enable specific microstructural and substructural features to be formed during the processing resulting in an unexpected combination of mechanical properties [2,3]. Formation of such structures in materials causes microstructural refinement to the ultrafine-grained (UFG) or even nanocrystalline (NC) area [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Severe plastic deformation (SPD) methods applied to metals enable specific microstructural and substructural features to be formed during the processing resulting in an unexpected combination of mechanical properties [2,3]. Formation of such structures in materials causes microstructural refinement to the ultrafine-grained (UFG) or even nanocrystalline (NC) area [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…ECAP has been successfully used over the last decade to insure the ultrafine-grained structures in a wide range of ductile metals including pure Cu and Cu alloys [4,5,[10][11][12][13]. Microstructure is refined to equiaxed subgrains/grains below 1 µm under high strains through simple shear, accompanied with a significant increase of strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3g) also confirmed that the recrystallization and grain growth mechanisms were prevalent at a temperature of 300°C. [45][46][47] explained that the dimple size of the UFG oxygen free high conductivity copper gradually decreases with increase in the strain rate. This is due to the increase in the brittleness with increase in the strain rate.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…The application of the severe plastic deformation (SPD) method in metals and metal alloys that have specific microstructural and design features may lead to high mechanical properties [2,3]. It is related to the strong refinement of the microstructure to the ultrafine-grained (UFG) or nanocrystalline (NC) level [4][5][6].…”
Section: Introductionmentioning
confidence: 99%